Long-Term Outcomes of Vital Pulp Therapy in Deep Carious Lesions Using Bioceramic Materials - Abdulmageed Alhusainy (Journal of Pharmacy and Bioallied Sciences)
Background: Vital pulp treatment (VPT) is an essential clinical intervention used to maintain the integrity of the tooth pulp in situations with severe carious lesions. Due to their bioactivity, sealing ability, and compatibility with pulp tissues, bioceramic materials have attracted considerable interest. Materials and Methods: This research included a sample of 100 individuals who had acquired deep carious lesions. The participants were randomly allocated into two groups: Group A (n = 50) had ventral prosthetic treatment (VPT) using a bioceramic material, whereas Group B (n = 50) underwent VPT with a traditional calcium hydroxide-based material. Initial, 6 months, 12 months, and 24 months after treatment, clinical and radiographic assessments were conducted. The main outcome measures consisted of dental pulp vitality, lack of discomfort, and radiographic evidence of the development of a hard tissue barrier. Results: By the 24-month follow-up, 92% of the teeth in Group A, which used bioceramic material, retained their pulp vitality, but just 80% of the teeth in Group B, which used calcium hydroxide, did the same. Significantly reduced rates of postoperative discomfort were seen in Group A (10%) compared to Group B (25%). The radiographic examination revealed that 88% of patients in Group A displayed effective creation of a hard tissue barrier, whereas only 72% of cases in Group B exhibited comparable results. Conclusion: The research verifies that bioceramic materials provide better long-term results in vital pulp treatment for severe carious lesions as compared to traditional materials based on calcium hydroxide.